Keeping the people's liberties : legislators, citizens, and judges as guardians of rights - Dinan, John J. (University Press of Kansas, 1998)
Which branch of government should be entrusted with safeguarding individual rights? Conventional wisdom assigns this responsibility to the courts, on the grounds that liberty can only be protected through judicial interpretation of bills of rights. In fact it is difficult for many people even to conceive of any other way that rights might be protected. John Dinan challenges this understanding by tracing and evaluating the different methods that have been used to protect rights in the United States from the founding until the present era. By analyzing the relative ability of legislators, citizens, and judges to serve as guardians of rights, Dinan's study demonstrates that each is capable of securing certain rights in certain situations.